Observations of tropospheric compounds at Evora station with multi-axis hyper spectral measurements - Bortoli, Daniele (2012)
The multi purpose UV-Vis. Spectrometer for Atmospheric Tracers Measurement (SPATRAM) is installed at the Observatory of the Geophysics Centre of Evora (38.5Âº N, 7.9Âº W) - Portugal, since 2004, measuring the zenith scattered radiation in the 300-550 nm spectral range. The main products are the total column and the vertical profiles of NO2 and O3 obtained with the application of the Differential Optical Absorption Spectroscopy (DOAS) algorithms and with inversion schemes based on the Optimal Estimation methods respectively. Recently (February 2009), the MIGE (Multiple Input Geometry Equipment) was coupled to the SPATRAM instrument allowing for the measurements of the diffused radiation in directions away from the zenith one (Off-Axis). MIGE is an alt-azimuth platform based on a very simple optical layout, using an optical fibre to transmit the radiation inside the monochromator of the SPATRAM equipment. Thanks to the solution adopted in the developing phase, MIGE is able to scan the whole hemisphere. In this work, after a brief description of the MIGE, the first and preliminary results for vertical profiles of NO2 in the Planetary Boundary Layer (PBL), and the values of Slant Column Densities (SCD) of O3 and SO2 measured in Off-Axis configuration at Evora Station, are presented and discussed.